2012
DOI: 10.1097/dad.0b013e3182473172
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Decidualized Endometriosis in a Nonpregnant Female

Abstract: Endometriosis is a disease process characterized by ectopic endometrial tissue. Involvement most commonly occurs in the lower pelvis, outside the uterine cavity, but can occur elsewhere, including the skin. Cutaneous endometriosis is a rare manifestation of this disease, with decidualization occurring in a very small minority of cases, almost always seen in pregnant females. Cutaneous involvement of endometriosis may present a diagnostic problem for the pathologist, particularly in the event of decidualization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…35,39,44,54,[56][57][58] If stroma is decidualized, it shows positivity for CD10, human placental lactogen, and inhibin-alpha. 49,50,59,60 Pan-cytokeratin expression was also examined by several authors, and they showed that it is variable from absent to diffusely positive. 15,50,59,60 If stroma is decidualized, the Ki-67 labeling index is also increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,39,44,54,[56][57][58] If stroma is decidualized, it shows positivity for CD10, human placental lactogen, and inhibin-alpha. 49,50,59,60 Pan-cytokeratin expression was also examined by several authors, and they showed that it is variable from absent to diffusely positive. 15,50,59,60 If stroma is decidualized, the Ki-67 labeling index is also increased.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,9,[11][12][13]15,17,19,[22][23][24][25]29,30,32,34,36,39,40,[49][50][51]53,57,59,60 All cases of cutaneous endosalpingiosis were found on previously unaffected skin. 1,61-63 Endometriosis usually presented on scars after gynecological surgical procedures-cesarean section (119 cases), 3,5,9,11,12,15,17,19,24,25,29,30,32,34,36,39,40,[49][50][51]53,57,59,60 episiotomy (13 cases), …”
Section: Discussionmentioning
confidence: 99%
“…Sometimes decidual cells may look like stony ring cells, but immunohistochemically, unlike carcinoma metastases, they are pancytokeratin-negative [2]. Decidual changes in AWE are also rare in the literature and are frequently reported as case reports [11,[13][14][15]. Decidual changes in our study were seen in 1 case.…”
Section: Discussionmentioning
confidence: 52%
“…Decidual changes usually occur in the presence of pregnancy [14,16]. However, such changes have been reported in patients who have not had previous pregnancy stories [15]. In our case, there was a cesarean story 3 years ago.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation